Speech Conflict in Family Communication - O. A. Mikhaylova (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The study was performed in line with the actual scientific areas of language conflictology and linguistic axiology. The article is devoted to the linguistic description of conflict situations in family communication by the material of the film “Inadequate people” (directed by Roman Karimov). The relevance of the study is due to the need to study communication in small social groups (in particular, in the family), as there is a high level of emotionality and intensity of communication, and it often becomes a conflictogenic factor. The text fragments representing speech conflicts between a teenager and adult relatives are analyzed. The markers of destructive communication and speech aggression in the communicative behaviour of adults (negatively charged language means and non-cooperative speech-behavioral tactics of condemnation, threat, coercion, etc.) and adolescents (high tone, insults, rude demand, disharmonizing strategy of discredit, tactics of “rudeness” and other). Special attention is paid to implicit speech aggression, which is embodied in irony, sarcasm, indirect issues. It is noted that using such techniques, the communicant expresses a negative or critical attitude towards the addressee. It is indicated that the intergenerational conflict is expressed in the deformation of interpersonal communication, in the failure of mechanisms of understanding between parents and children, in disagreements concerning moral and value orientations.